2014
DOI: 10.1144/sp406.1
|View full text |Cite
|
Sign up to set email alerts
|

Repeated injection of hydrothermal fluids into downdip carbonates: a diagenetic and stratigraphic mechanism for localization of reservoir porosity, Indian Basin Field, New Mexico, USA

Abstract: A detailed study of the Pennsylvanian Indian Basin Field of New Mexico, USA is used to develop a conceptual model that predicts reservoir porosity in clean down-depositional-dip marine carbonate, where repeated fracturing allows for hydrothermal fluid flow. Strata updip probably experienced repeated events of subaerial exposure, resulting in mineralogical stabilization and extensive calcite cementation that prevented extensive hydrothermal alteration. Clean, carbonate sediment deposited downdip was more prone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…In addition to the role of these faults in channelizing the fluids, their mobilization must have been intensified by some deriving mechanisms. A thermal convection system derived from high hit flux during rifting was interpreted by Hollis et al (2017) to be responsible for circulation of seawater in a syn-rift dolomitization case in the Hammam Faraun fault block (Suez Rift, Egypt). In such a scenario, the salinity of the fluids and their 87 Sr/ 86 Sr ratios are expected to be more or less within the range of seawater.…”
Section: Timing and Structural Controls On The Evolution Of Parental mentioning
confidence: 99%
“…In addition to the role of these faults in channelizing the fluids, their mobilization must have been intensified by some deriving mechanisms. A thermal convection system derived from high hit flux during rifting was interpreted by Hollis et al (2017) to be responsible for circulation of seawater in a syn-rift dolomitization case in the Hammam Faraun fault block (Suez Rift, Egypt). In such a scenario, the salinity of the fluids and their 87 Sr/ 86 Sr ratios are expected to be more or less within the range of seawater.…”
Section: Timing and Structural Controls On The Evolution Of Parental mentioning
confidence: 99%
“…Hydrothermal‐ related and fracture‐related, vuggy and late diagenetic dissolution pores are presumably related to the burial corrosion (for example, BSR and TSR) and hydrothermal events. The corrosion fabrics are commonly observed in the platform facies in the Upper Cambrian strata and are probably related to the regional hydrothermal activity (Davies & Smith, ; Saller & Dickson, ; Dong et al ., ; Hiemstra & Goldstein, ; Jiang et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The amount of porosity found in deeply buried (>3500 m) dolostone reservoirs is usually considered to be a complex function of the primary porosity, the amount of secondary porosity due to the 'mole for mole' replacement or dissolution of calcite or aragonite by dolomite, and the degree of preservation of early diagenetic porosity (Sun, 1995;Machel, 2004;Ehrenberg et al, 2006Ehrenberg et al, , 2012. Some have recently argued that significant porosity could be newly formed or pre-existing porosity redistributed due to the dissolution of dolomite and anhydrite in deeply buried dolostone reservoirs due to TSR (Cai et al, 2014), as well as due to hydrothermal dolomitization, fluids mixing and cooling, fracture system formation and brecciation (Qing & Mountjoy, 1994;Sun, 1995;Corbella et al, 2004;Machel, 2004;Davies & Smith, 2006;Smith, 2006;Saller & Dickson, 2011;Gomez-Rivas et al, 2014;Hiemstra & Goldstein, 2015;Jiang et al, 2015b;Mart ın-Mart ın et al, 2015). It is probable that more than one of the above diagenetic processes has affected reservoir quality in the Cambrian reservoirs in the Tarim Basin.…”
Section: Porous Dolostone Reservoirsmentioning
confidence: 99%
“…RTM is increasingly used to analyse the evolution of reservoir quality in an attempt to predict porosity and permeability away from wells (e.g. , 2013Whitaker & Xiao 2010;Xiao et al 2013;Corbella et al 2014;Pal et al 2014), adding value to studies that constrain porosity evolution using geological and geochemical techniques (Ramaker et al 2014;Hiemstra & Goldstein 2014;Li et al 2014). Yet, comparisons between well-calibrated laboratory experiments and numerical simulations in carbonate rocks have shown that RTM is able to match experimental observations at best qualitatively .…”
Section: Fundamental Controls On Fluid Flow In Carbonatesmentioning
confidence: 99%
“…For example (e.g. Hiemstra & Goldstein 2014;Ramaker et al 2014), can diagenesis in carbonate reservoirs be categorized by levels of complexity of diagenesis? When is it important to include diagenetic details or when can they be readily ignored in representations of reservoir quality in reservoir simulations?…”
Section: Background and Challengesmentioning
confidence: 99%